2016
DOI: 10.1177/0734282916639195
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Accuracy in Prekindergarten Teacher Ratings of Students’ Mathematics Skills

Abstract: The No Child Left Behind Act requires that 95% of students in all public elementary and secondary schools are assessed in mathematics. Unfortunately, direct assessments of young students can be timely, costly, and challenging to administer. Therefore, policy makers have looked to indirect forms of assessment, such as teachers’ ratings of student skills, as a substitute. However, prekindergarten teachers’ ratings of students’ mathematical knowledge and skills are only correlated with direct assessments at the .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
2
22
0
4
Order By: Relevance
“…Teacher education and years of experience were not related to teacher accuracy in the current study. Previous research has reported similar negative findings with respect to these variables (Furnari et al., ), or mixed minor effects with higher teacher education actually being associated with less judgment accuracy (overestimation) for some student subgroups (Ready & Wright, ). Thus, general educational attainment by teachers, as measured in these studies (e.g., degree achieved), does not appear to enhance judgment accuracy.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Teacher education and years of experience were not related to teacher accuracy in the current study. Previous research has reported similar negative findings with respect to these variables (Furnari et al., ), or mixed minor effects with higher teacher education actually being associated with less judgment accuracy (overestimation) for some student subgroups (Ready & Wright, ). Thus, general educational attainment by teachers, as measured in these studies (e.g., degree achieved), does not appear to enhance judgment accuracy.…”
Section: Discussionmentioning
confidence: 62%
“…Agreement between teachers’ judgments and the performance measure was lower for math skills ( r = .47, mean percent = 66%). Previous research has reported similar levels of agreement for pre‐K math (i.e., r = .50; Furnari et al., ; and r = .53, Kilday et al., ), suggesting that pre‐K teachers’ judgments may be less accurate in this domain. Whereas this decrement in math accuracy, relative to language arts, does not appear to be true of teachers working with older students (Südkamp et al., ), research indicates that pre‐K teachers view math as less important to teach than literacy (Ginsburg, Lee, & Boyd, ; Kowalski et al., ) and spend less time teaching it (Cross, Woods, & Schweingruber, ).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This issue is especially salient when discussing KEAs, as many of these measures rely on observational rubrics as opposed to direct assessments and thus may be unfamiliar to the kindergarten teachers who are tasked with administering them (Butts, ; Schultz, ; Weisenfeld, ). Moreover, the process of making reliable judgments about students' skills based on a rubric or rating scale can be challenging for many teachers (Cabell, Justice, Zucker, & Kilday, ; Furnari, Whittaker, Kinzie, & DeCoster, ; Kilday, Kinzie, Mashburn, & Whittaker, ; Mashburn & Henry, ; Waterman, McDermott, Fantuzzo, & Gadsden, ). Rubric or rating scale reliability can be affected if the scores are perceived to contribute to some type of consequential decision for the student, teacher, or program, as well (Harvey, Fischer, Weieneth, Hurwitz, & Sayer, ; Waterman et al, ).…”
Section: Assessment‐ and Assessor‐related Validity And Reliability Chmentioning
confidence: 99%